4x-(x+3)=-16

Simple and best practice solution for 4x-(x+3)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-(x+3)=-16 equation:


Simplifying
4x + -1(x + 3) = -16

Reorder the terms:
4x + -1(3 + x) = -16
4x + (3 * -1 + x * -1) = -16
4x + (-3 + -1x) = -16

Reorder the terms:
-3 + 4x + -1x = -16

Combine like terms: 4x + -1x = 3x
-3 + 3x = -16

Solving
-3 + 3x = -16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3x = -16 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = -16 + 3
3x = -16 + 3

Combine like terms: -16 + 3 = -13
3x = -13

Divide each side by '3'.
x = -4.333333333

Simplifying
x = -4.333333333

See similar equations:

| 10(j+1)=100 | | 2(3.5*3.11+6)=2.5*3.11-2 | | -2(5t-5)+8t=2t-5 | | y+7=4(y-2) | | 5x(2x+1)=50 | | 3u-20=13 | | 0=(x^2)-4x+2 | | X-5(x-3)=2(x-10) | | 29.75m+0.15p=19.95m+0.29p | | 3(3-1)=4(3-15) | | 20=a/-4 | | 4(12.5-2)=3(1.5+12.5) | | 1x-3=6 | | 4(12.5-2)=3(1.5+x) | | 5x-11=12x+9 | | 20=9/-4 | | x+2-5x=18 | | 4r-3.8=2.2+2r | | 3(18+22)=4(18+12) | | -((x^2)-4x-5)=7 | | 6(2x)=3x+9 | | 3.2a-2=30 | | 5x^2+7x+56=70 | | 13lnx^2-lnx^24=ln(4x+12) | | 3x-2.6=c+8.2 | | x+0.17x=140 | | 4/3•3/7 | | 40a/190a | | -n-6=6 | | 6(3*2.5+5)=75 | | (4a)(5a-3)= | | 1/3b=8=1/2b-4 |

Equations solver categories